The post-septic peripheral myeloid compartment reveals unexpected diversity in myeloid-derived suppressor cells - Barrios, Evan L.; Leary, Jack R.; Darden, Dijoia B.; Rincon, Jaimar C.; Willis, Micah; Polcz, Valerie E.; Gillies, Gwendolyn S.; Munley, Jennifer A.; Dirain, Marvin L.; Ungaro, Ricardo; Nacionales, Dina C.; Gauthier, Marie-Pierre L.; et al. (Frontiers in Immunology, 2024)
Sepsis engenders distinct host immunologic changes that include the expansion of myeloid-derived suppressor cells (MDSCs). These cells play a physiologic role in tempering acute inflammatory responses but can persist in patients who develop chronic critical illness. The origins and lineage of these MDSC subpopulations were previously assumed to be discrete and unidirectional; however, these cells exhibit a dynamic phenotype with considerable plasticity. Using Cellular Indexing of Transcriptomes and Epitopes by Sequencing followed by transcriptomic analysis, we identify a unique lineage and differentiation pathway for MDSCs after sepsis and describe a novel MDSC subpopulation. Additionally, we report that the heterogeneous response of the myeloid compartment of blood to sepsis is dependent on clinical outcome.